Competitive ability of wheat (Triticum aestivum) cultivars against wild oat (Avena ludoviciana) infestation under zero tillage - MISHRA, J S; SINGH, V P (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was conducted during winter (rabi) season of 2003–04 and 2004–05 on a Typic Chromusterts soils at Jabalpur to evaluate the ability of different winter wheat (Triticum aestivum L. emend. Fiori & Paol.) cultivars to compete against wild oats [Avena sterilis ssp ludoviciana (Dur.) Gill & Magne] in zero-till conditions. Wild oat reduced wheat grain yield by 39–69% depending on cultivars. Wild oat dry matter ranged from 90 to 143 g/m2 in wild oat infested plots. Application of clodinafop 60 g/ha gave effective control of wild oats. The decrease in wild oat dry weight due to clodinafop was however more (92%) in ‘Raj 3777’ and least (64%) in ‘DL 788-2’. Wheat cultivars ‘Sonalika’, ‘Sujata’, ‘HD 2285’ and ‘PBW 343’ gave the maximum (2 275, 2264, 2256 and 2234 kg/ha) and ‘DL 803- 3’ the minimum (1 333 kg/ha) grain yields in wild oat infested plots. Wheat leaf area, plant dry weight and number of spikes were better characters than plant height for predicting competitive ability of wheat cultivars to wild oat as these parameters were significantly negatively correlated with wild oat dry weight. Wheat cultivars ‘Sonalika’, ‘Sujata’, ‘HD 2285’ and ‘PBW 343’ performed better in wild oat infested areas and clodinafop 60 g/ha at 30 days after sowing provided effective control of wild oats in zero-till wheat.